Efficacy of betel leaves, Piper betle L. crude extract on Vibrio alginolyticus in cultured Asian seabass, Lates calcarifer (Bloch, 1790) - Othman, Ahmad Baihaqi (2018)
Production of Asian seabass, Lates calcarifer is facing a crucial problem due to vibriosis caused by Vibrio alginolyticus. The current treatment using commercial antibiotic is not encouraged due to the issue of antibiotic resistant bacteria. Betel leaf, Piper betle has been known to contain various active compounds that are effective against bacterial infection and maintain the fish health. This study used several compounds for extraction medium of the active compounds of betel leaf. Ethanol has been concluded as the best solvent for the extraction of the active ingredients of betel leaf. The ethanoic crude extract showed inhibition zone of 21 mm compared with aques extraction with 9 mm (p<0.05). Results of the minimum inhibitory concentration (MIC) test indicate that the extract could inhibit Vibrio alginolyticus at a concentration of 0.2 mg/mL and could kill the bacteria at concentration of 0.39 mg/mL (MBC). The palatability test revealed that the seabass could consume 100% of the crude extract as high as 200mg/kg of feed for over 7 days without showing abnormality. Next, the challenge test was done in two trials to test the crude extract as preventive and as treatment against vibriosis due to Vibrio alginolyticus. For the preventive test, the fish were fed with crude extract at 100mg/kg of feed before being infected with Vibrio alginolyticus. For the treatment test, the fish were initially infected with Vibrio alginolyticus before being treated with crude extract at the same dose of 100mg/kg of feed. The results revealed that both preventive and treatment trials produced significantly (p<0.05) higher survival rate compared with oxytetracycline. These results showed that the betel leaf crude extract is highly potential to be used as preventive measure against vibriosis.